Atomically Tailored Zn-ZIF-8 via RuNi Nanoalloy Replacement for Improved Photocatalytic H2 Evolution - Jamma A.; Vennapoosa C.S.; Annadata H.V.; Ghosh B.; Govu R.; Aggarwal H.; Ahmadipour M.; Abraham B.M.; Wang X.; Pal U. (American Chemical Society, 2025)
In this study, we developed a solid-state atomic replacement method for metal catalysts, enabling the exchange of metal atoms between single atoms and nanoalloys to create new combinations of nanoalloys and single atoms. We observed that partial metal interchange occurred between the RuNi nanoalloy and Zn from the zeolitic imidazolate framework-8 (ZIF-8) on a carbon-nitrogen framework (CNF) at a high temperature of 900 C, leading to the creation of RuZn nanoparticles and single nickel atoms (Ni-CN). Extended X-ray absorption fine structure (EXAFS) and X-ray absorption near edge structure (XANES) analyses revealed that Ni is atomically dispersed within (RuZn)/Ni-CN. This finding confirms the migration of Zn and Ni during the pyrolysis of the RuNi@ZIF-8 precursor, providing definitive evidence of atomic replacement. Due to the synergistic influence of RuZn nanocrystals and Ni-CN, the resulting (RuZn)/Ni-CN multisite catalyst exhibited superior hydrogen evolution reaction (HER) ability compared to the conventional nanoalloy-based catalysts. Density functional theory calculations revealed that the integration of the (RuZn)n cluster on Ni surrounded with different N-coordinated carbon structures enhanced HER activity with the optimized (RuZn)n/NiN2C2 catalyst exhibiting a low ?GH and improved electron charge redistribution, thereby promoting favorable hydrogen adsorption. Our findings provide valuable insights into the design and optimization of photocatalysts through atomic-level engineering, opening new avenues for efficient and sustainable energy conversion technologies. ? 2024 American Chemical Society.